2018
DOI: 10.1139/cjps-2017-0070
|View full text |Cite
|
Sign up to set email alerts
|

A 1-deoxy-d-xylulose 5-phosphate reductoisomerase gene probably involved in the synthesis of terpenoids in Chrysanthemum indicum var. aromaticum

Abstract: Terpenoids are important secondary metabolites in plants. The synthesis of terpenoids involves a key enzyme, 1-deoxy-d-xylulose 5-phosphate reductoisomerase (DXR). In an aromatic ornamental plant, Chrysanthemum indicum var. aromaticum, terpenoids were found to be an important component in leaf secretions. To study the regulatory mechanism of terpenoid synthesis in C. indicum var. aromaticum, we cloned the DXR gene from C. indicum var. aromaticum, named CiDXR, based on transcriptome data. CiDXR is 1419 bp, enco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…It was shown that the expression of PdDXR increased and then decreased after both 1 mM MeJA treatment and mechanical damage treatment of P. densiflora [19]. Dendranthema indicum DiDXR could be induced by 0.25% MeJA activation up to a 20-fold expression after 24 h [35]; GmDXR expression was significantly higher in Gentiana macrophylla leaf tissue after 2 d treatment with the hormone [36]. The expression of AoDXR in the rootstock of Alpinia officinarum was 1.8-fold higher than the control after 12 h of spraying with 10 µM MeJA [37].…”
Section: Discussionmentioning
confidence: 97%
“…It was shown that the expression of PdDXR increased and then decreased after both 1 mM MeJA treatment and mechanical damage treatment of P. densiflora [19]. Dendranthema indicum DiDXR could be induced by 0.25% MeJA activation up to a 20-fold expression after 24 h [35]; GmDXR expression was significantly higher in Gentiana macrophylla leaf tissue after 2 d treatment with the hormone [36]. The expression of AoDXR in the rootstock of Alpinia officinarum was 1.8-fold higher than the control after 12 h of spraying with 10 µM MeJA [37].…”
Section: Discussionmentioning
confidence: 97%
“…Doxorubicin (DXR) is an anthracycline anticancer drug that is an important part of several chemotherapy regimens for small-cell lung and breast cancer. Several potential medicinal plants in Indonesia contain doxorubicin, such as Curcuma xanthorrhiza, C. longa, Z. officinale (Family: Zingiberaceae) (Ajith et al 2016); Chrysanthemum indicum (Family: Asteraceae) (Gao et al 2018); Cymbopogon winterianus (Family: Poaceae) (Devi et al 2015); Digitalis purpurea L. (Family: Plantaginaceae) (Rad et al 2020); and Santalum album (Family: Santalaceae) (Zhang et al 2021). DXR is the best channelizer for metastatic thyroid cancer (Venkatesh et al 2007), although DXR can increase chromatid, micronuclei, and chromosome abnormalities, as well as single-strand and double-strand DNA breaks (Dhawan et al 2003).…”
Section: Doxorubicin-coding Dxr Genementioning
confidence: 99%
“…The fraction of DXP employed for terpenoid synthesis is determined by the degree of DXR activeness (Koo et al 2013). Recent research has shown that DXR regulates isoprenoid formation in crops and plays a key role in management thoughout the process (Devi et al 2015;Gao et al 2018;Rad et al 2020). The DXR gene was extracted from H. annuus L. plants and evaluated for genotoxicity using micronuclei in mouse bone marrow.…”
Section: Doxorubicin-coding Dxr Genementioning
confidence: 99%
“…Terpenoids, as naturally occurring phytochemicals, contribute to normal plant growth and development and play crucial roles in plant interactions with environmental stresses [ 11 ]. They include diverse classes of primary and secondary metabolites such as phytohormones, photosynthetic pigments and essential oils [ 12 , 13 ]. It was reported that L. arabicus L. contains high levels of the terpenoid sitosterol, which has many health benefits [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the enzymatic chloroplast pathway, a main upstream enzyme, deoxyxylulose phosphate reductoisomerase (DXR), is known to catalyze the reduction of deoxyxylulose phosphate (DXP) to MEP, which is oxidized to isopentenyl pyrophosphate (IPP), the common precursor of terpenoid biosynthesis. DXR activation has been reported to promote terpenoid pathways as a key regulatory enzyme controlling their synthesis [ 13 , 15 ].…”
Section: Introductionmentioning
confidence: 99%